Current Approaches in Management of Patients with Hypophosphatasia - Alexander A. Baranov; Leyla S. Namazova-Baranova; Sergey I. Kutsev; Tea V. Margieva; Nato D. Vashakmadze; Elena A. Vishneva; Lilia R. Selimzyanova; Elena Yu. Voskoboeva; Ekaterina Yu. Zakharova; Ludmila M. Kuzenkova; Tina V. Lobzhanidze; Lyudmila K. Mikhaylova; et al. (Union of pediatricians of Russia, 2021)
he authors present the latest data on the hypophosphatasia (HPP) management in children. Hypophosphatasia is a rare genetic disease caused by deficiency of tissue-specific alkaline phosphatase due to mutation in the ALPL gene. The article covers all the features of epidemiology, etiology and pathogenesis, detailed stages of differential diagnostics. Treatment guidelines for pediatric patients are provided, they are based on the principles of evidence-based medicine. Special attention was given to the only effective method of hypophosphatasia management -enzyme replacement therapy (ERT). This material is the clinical guideline draft for the management of patients with hypophosphatasia prepared by the Union of Pediatricians of Russia and the Association of Medical Geneticists.